STUDI NUMERIK PENGARUH JUMLAH DAN PUNTIRAN SWIRLER VANES PADA ALIRAN MASUK TABUNG - Parwatha, I Gede; Hartono, Firman; Pasaribu, Hisar M; Sardjadi, Djoko; Suwono, Aryadi (Mesin, 2005)
Flow field at the inlet of a combustor under the influence of swirler vanes was investigated computationally. The isothermal flow was examined to predict the combustion stability. The simulations indicate different flow-field characteristics can be achieved under the same swirl number. In addition to swirl number, swirl velocity induces the existence of centrifugal force. This force affect velocity profile peak, static pressure profile, radially; and recirculation zone, axially.